IMPLEMENTATION OF QUALITY MANAGEMENT SYSTEM ISO 9001:2008 IN IMPROVING TEACHER PERFORMANCE IN SMA DARUL ULUM 2 UNGGULAN BPPT JOMBANG - Rihatul Jannah (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2021)
The ISO 9001:2008 quality management system is one of the implementation forms of total quality management (TQM) concept. This total quality management system requires an organization to have standards such as resource management standards, product realization, measurement and evaluation, and documentation system. The purpose of ISO 9001:2008 quality management systemis toimprovecustomer satisfaction by fulfilling customer requerements through complete facilities, profesional teachers, achievement improvement and many others. This research used qualitative approach with field research design. The results obtained that performance of theachers in SMA Darul Ulum 2 Unggulan BPPT Jombang has a good predicate and implementation of ISO 9001:2008 quality management system run well with the commitment of school principals and all the citizens of the school, and take the field. the ISO allows teachers to continue to learn and improve performance. That is also supported by commitment from high school princupals and high schoolcommunity by continuously improving the quality of work and there is a complete facility to facilitate school activities. so far, not many obstacles are heavy when schools use the ISO 9001:2008 management system, it just takes adjustment for each member to use this ISO management system.